Contextual and Individual-Level Determinants of Physicians’ Acceptance of Electronic Medical Records: A Systematic Review Across Diverse Health Systems - Satria, Alfan; Imran, Abdul Waris; Yacobus, Danny Jaya; Suryana, Hari; Yuliaty, Farida (Riviera Publishing, 2025)
The application of Electronic Medical Records (Rekam Medis Elektronik, RME) has great potential to improve the quality of health services, but the rate of acceptance by physicians still varies across different contexts. This study aims to identify individual and contextual factors that influence the acceptance of RME by physicians based on recent empirical studies. A systematic review was conducted through an article selection process using Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). Articles were systematically searched using the keywords: